Analisis Kinerja Keuangan Perusahaan Dengan Menggunakan Metode EVA Pada Perusahaan Sektor Konsumen Primer Yang Terdaftar Di JII - Dwi Mulya, Khairunnisa; Kristianingsih (Journal of Applied Islamic Economics and Finance, 2024)
The purpose of this study was to analyze the financial performance of primary consumer sector companies listed in the Jakarta Islamic Index (JII) from 2012 to 2021, using the Economic Value Added (EVA) method. The researchers utilized a purposive sampling method to select a sample of three companies consistently registered in the JII. The necessary data for the analysis, including balance sheets and income statements, were collected from the official websites of the respective companies. Microsoft Excel was employed as the tool to calculate the company's performance evaluation using the EVA method. The findings from this comprehensive study over the 2012-2021 period indicate that the three primary consumer sector companies listed in the JII demonstrated consistently positive financial performance (EVA>0) and generated significant economic value year after year.